2019
DOI: 10.1177/0972652719880153
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment Determinants in Oil Exporting Countries: Revisiting the Role of Natural Resources

Abstract: This article explores the determinants of foreign direct investment (FDI) in oil-dependent economies and revisits the role of natural resources in attracting FDI to countries of this kind. Panel data from the six Gulf Cooperation Council (GCC) countries, namely Bahrain, Kuwait, Oman, Qatar, Saudi Arabia and the United Arab Emirates, have been employed, covering the period from 1990 to 2015. First, we investigate the FDI determinants during the entire sample period, and then run another investigation starting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 54 publications
2
18
0
Order By: Relevance
“…Such as Sahu ( 2020), Alfalih and Bel Hadj (2020), Maryam and Mittal (2020), and Saini and Singhania (2018). Similarly, Eissa and Elgammal (2019) also ascertained that in oil-rich countries such as Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates, trade openness is one of the essential factors which determine the FDI inflows.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Such as Sahu ( 2020), Alfalih and Bel Hadj (2020), Maryam and Mittal (2020), and Saini and Singhania (2018). Similarly, Eissa and Elgammal (2019) also ascertained that in oil-rich countries such as Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates, trade openness is one of the essential factors which determine the FDI inflows.…”
Section: Discussionmentioning
confidence: 96%
“…Which in turn, will leads FDI inflows into a higher level due to the small investment risk. Moreover, Eissa and Elgammal (2019) revealed that in oil-rich countries, which is also a member of OIC countries, human resource quality, which reflected by the labour force, has a negative and insignificant correlation with FDI. The author explained that labour nationalisation policy has created several policies in order to increase the secure jobs which benefit to national.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations